The satirical Tang poetry in Vietnam of the middle ages - Trần, Thị Lệ Thanh; Nguyễn, Thu Hà (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2020)
Looking back at the history of Vietnamese literature in medieval times, it can be seen that the Tang poetry has a very good relationship with the type of satirical poetry. This article identifies the process of formation and development of the satirical Tang poetry in Vietnam of the middle ages from the Xth century to the end of the XIXth century, be based on that, recognizing the contribution of this through some outstanding names in the type of Tang poetry in Vietnam.